Pembentukan Identitas Manusia melalui Narasi dalam Konteks Pendidikan menurut Paul Ricoeur - Sergius Lay; Tinambunan, Laurentius; Ndoa, Paulinus Kanisius; Marbun, Martina Rosmaulina; Br Ginting, Elisa (Jurnal Riset Rumpun Agama dan Filsafat, 2025)
This article is a literature review that examines Paul Ricoeur’s concept of narrative identity and its relevance to education. Ricoeur conceives human identity as a dynamic construction shaped through narrative, namely the reflective interpretation of life experiences within the dimensions of time, social relations, and self-awareness. In this framework, education is not merely understood as a means of knowledge transmission but also as a hermeneutical space where learners construct an understanding of themselves through experience, reflection, and dialogue. Narrative enables students to coherently connect the past, present, and future, while simultaneously cultivating character, responsibility, and empathy. This article highlights the importance of narrative-based learning strategies, such as case studies, autobiographical writing, analysis of literary and historical texts, and project-based learning. Through these approaches, students are encouraged to develop a reflective and ethical identity that is open to diversity. Thus, Ricoeur’s thought provides a strong philosophical foundation for building humanistic character education in which learners are positioned as subjects who grow and transform through their own life stories.